2019
DOI: 10.3897/zse.95.31726
|View full text |Cite
|
Sign up to set email alerts
|

Herpetological surveys in two proposed protected areas in Liberia, West Africa

Abstract: In March and April 2018 we surveyed amphibians and reptiles in two Proposed Protected Areas (PPAs) in Liberia. In the Krahn-Bassa Proposed Protected Area (KBPPA) in eastern Liberia 36 species of amphibians and 13 species of reptiles were recorded. In the Foya Proposed Protected Area (FPPA) in western Liberia 39 species of amphibians and 10 species of reptiles were recorded. The encountered herpetological communities in both sites were typical for West African rainforests. However, some species indicated distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Diversity hotspots in anuran species are commonly found in forests that offer a very rich ecosystem for arboreal species (Nago et al 2006; Rödel and Ernst 2003; Rödel et al 2007; Rödel and Glos 2019); this was confirmed by our data. The forests in this region show very weak or almost non-existent human influence; and if conserved, provide ideal environments for anuran species.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Diversity hotspots in anuran species are commonly found in forests that offer a very rich ecosystem for arboreal species (Nago et al 2006; Rödel and Ernst 2003; Rödel et al 2007; Rödel and Glos 2019); this was confirmed by our data. The forests in this region show very weak or almost non-existent human influence; and if conserved, provide ideal environments for anuran species.…”
Section: Discussionsupporting
confidence: 89%
“…A large portion of the litter and leaves were wet on the ground, making it possible to observe a large number of anurans living on the ground in the litter, in the stilt roots of the trees, and on the wet tree trunks near the ground. Diversity hotspots in anuran species are commonly found in forests that offer a very rich ecosystem for arboreal species (Nago et al 2006;Rödel and Ernst 2003;Rödel et al 2007;Rödel and Glos 2019); this was confirmed by our data. The forests in this region show very weak or almost non-existent human influence; and if conserved, provide ideal environments for anuran species.…”
Section: Abiotic Variables Of Anuran Sampling Environmentssupporting
confidence: 88%
See 3 more Smart Citations